The effect of corporate social responsibility on trustful relationship, supportive communication intention, and brand loyalty of ethnic halal restaurants - Toshmirzaev, Davron; Ahn, Young-joo; Kiatkawsin, Kiattipoom; Sutherland, Ian; Zielinski, Seweryn (Frontiers in Psychology, 2022)
The purpose of this study is to examine the relationships among CSR activities, brand trust, supportive communication intention, and brand loyalty in a halal restaurant franchise. This study attempts to understand the brand loyalty formation among foreigners visiting a halal ethnic restaurant franchise in South Korea. This study can contribute to the body of empirical evidence showing that CSR activities for different stakeholders can increase brand loyalty mediated by trust. One of the largest ethnic halal restaurant franchises is chosen as a case study in Korea. A total of 225 questionnaires were used for final analysis. This study used a structural equation model. The results reveal that CSR activities include four constructs, namely, CSR activities to community, to employee, to environment, and to customers. These four dimensions reflect voluntary activities for core stakeholders and are positively associated with enhancement of trustful relationships between customers and restaurants. Among four CSR dimensions, CSR activities to employee is the most influential dimension, followed by CSR to community and to environment. However, the insignificant effect of CSR activities to customers on trust is found. Furthermore, trust positively influences supportive communication intention and brand loyalty. The proposed model of this present study can shed light on how to enhance brand loyalty and sustain trustful and emotional value of an ethnic restaurant franchise. The results can provide important implications for planning CSR engagement from a practical and managerial perspective in the restaurant industry.